Model Pengembangan Ekowisata Berbasis Destination Management Organizations untuk Percepatan Ekonomi Desa di Zona Timur Kabupaten Malang - Supriadi, Bambang (Relasi : Jurnal Ekonomi, 2021)
Malang Regency has considerable ecotourism potential, but its contribution to community welfare is still low. This research aims to develop a strategic model for managing Poncowismojatu ecotourism based on Destination Management Organizations (DMOs) to increase tourism competitiveness and encourage rural economic growth in Malang Regency. This research uses a qualitative descriptive method with a SWOT analysis approach. The source of informants as a research sample of 30 respondents includes tourists, local communities, tourism managers, and government representatives. Data were collected through questionnaires and then analyzed to evaluate ecotourism management's strengths, weaknesses, opportunities, and threats. The results showed that implementing DMOs improved the quality of ecotourism services by optimizing cross-sector coordination, increasing the effectiveness of tourism marketing, and strengthening community participation in destination management. The DMOs-based management model contributes to increased tourist visits and customer satisfaction, which positively impacts the local economy. However, the main challenges are the lack of supporting infrastructure and low community awareness of environmental sustainability. The results of this study have contributed to increasing the capacity of human resources in tourism, strengthening marketing strategies, and optimizing infrastructure that supports sustainable ecotourism. Additionally, implementing DMOs will increase regional tourism's competitiveness and provide sustainable economic and ecological benefits.